A method for firing a glass insulating layer on the surface of oxygen-free copper

By using glaze immersion and firing technology to form a high-density glass insulating layer on the surface of oxygen-free copper, the problems of high secondary electron emission coefficient, low bonding strength, poor high temperature and high pressure resistance and insufficient plasma sputtering resistance in the prior art are solved, and more efficient insulation performance and stronger bonding force are achieved.

CN115725823BActive Publication Date: 2025-04-25INST OF ENERGY HEFEI COMPREHENSIVE NAT SCI CENT (ANHUI ENERGY LAB)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211638426.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-19
Publication Date
2025-04-25
Estimated Expiration
2042-12-19

AI Technical Summary

Technical Problem

When the insulating layer is attached to the surface of oxygen-free copper, the secondary electron emission coefficient is high, the bonding strength is low, the high temperature and high pressure resistance is poor, and the plasma sputtering resistance is insufficient.

Method used

The glaze immersion method is used to glaze the surface of the oxygen-free copper after grinding, annealing and pickling, and the pre-prepared glaze is used to fire in an argon atmosphere to form a high-density glass insulating layer.

Benefits of technology

The high-temperature and high-pressure performance of the oxygen-free copper surface insulating layer is achieved, the secondary electron emission coefficient is reduced, the bonding strength with the copper surface is enhanced, and the plasma sputtering resistance is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a method for firing a glass insulating layer on the surface of oxygen-free copper, wherein silicon dioxide, aluminum oxide, zirconium oxide, sodium oxide, potassium oxide, and titanium dioxide powders are mixed according to a certain specific gravity and water is added to prepare a glaze, and the oxygen-free copper after grinding, annealing, and pickling is glazed by dipping, and then fired in an argon atmosphere. The obtained glass insulating layer has the characteristics of high bonding strength with the copper surface, low sputtering of the glass insulating layer in a plasma discharge cavity, high withstand voltage, and easy industrial processing, and the method is applicable to both flat copper and curved copper, and has great application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal surface insulating material processing, in particular to a method for sintering a glass insulating layer on the surface of oxygen-free copper. Background Art

[0002] With the rapid development of built-in inductively coupled ion sources, new requirements have been put forward for the insulating layer on the surface of oxygen-free copper. It is urgently required that the insulating layer on the copper surface has the characteristics of high temperature resistance, high voltage resistance, low secondary electron emission coefficient, plasma sputtering resistance, and high bonding strength.

[0003] In the prior art, an insulating layer is generally attached to the copper surface by two technical means: glass powder sintering and magnetron sputtering coating. As for the glass powder sintering method: on the one hand, the glass powder needs to be treated with organic glue before sintering to adhere to the copper surface for sintering. The use of organic glue will introduce carbon-containing impurities and increase the secondary electron emission coefficient of the insulating layer surface; on the other hand, the glass layer formed by sintering has a low bonding strength with the copper surface. Due to the difference in stress between copper and glass, it is easy to cause the glass layer to fall off during use. In addition, for magnetron sputtering, the insulating material (such as aluminum oxide) plated by magnetron sputtering is generally several microns, which is difficult to withstand very high voltages, and the insulation performance gradually decreases during long-term use.

[0004] In view of the above problems, the present invention proposes a method for firing a glass insulating layer on the surface of oxygen-free copper, which can produce a glass insulating layer that is resistant to high temperature, high pressure, low secondary electron emission coefficient, plasma sputtering, and has high bonding strength with the copper surface, so as to meet the special application requirements in the fields of built-in inductively coupled radio frequency ion source accelerator, ion cleaning, etc. Summary of the invention

[0005] The purpose of the present invention is to provide a method for firing a glass insulating layer on the surface of oxygen-free copper, which can produce a glass insulating layer on the copper surface that is resistant to high temperature, high pressure, low secondary electron emission coefficient, plasma sputtering, and has high bonding strength with the copper surface, and can meet special application requirements in the fields of built-in inductively coupled radio frequency ion source accelerators, ion cleaning, etc.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A method for firing a glass insulating layer on the surface of oxygen-free copper comprises the following steps:

[0008] (1) grinding the surface of oxygen-free copper; placing the ground oxygen-free copper in a heating furnace in an argon atmosphere for annealing; immersing the annealed oxygen-free copper surface in a copper acid polishing solution for 40-60 seconds for pickling;

[0009] (2) immersing the pickled oxygen-free copper into a pre-prepared first-density glaze for glazing treatment; after the copper treated in the first-density glaze is naturally air-dried, immersing it into a pre-prepared second-density glaze for secondary glazing treatment;

[0010] (3) The oxygen-free copper surface after the secondary glaze treatment is naturally air-dried and then placed in a heating furnace for vacuum sealing;

[0011] (4) After the vacuum degree in the heating furnace is evacuated to below 1Pa, the heating program is started; when the temperature in the heating furnace rises to 290-300°C, the vacuum angle valve is closed to stop evacuation, and then argon gas is filled into the heating furnace to 0.05-0.07MPa; the heating furnace continues to heat up to 890-900°C and maintains for 5-10 minutes before naturally cooling down; after naturally cooling down to 50°C, the oxygen-free copper is taken out, and the work of firing the insulating glass layer on the surface of the oxygen-free copper is completed.

[0012] The surface of the oxygen-free copper is polished with metallographic sandpaper, wherein the metallographic sandpaper is 2000 mesh and the abrasive is aluminum oxide.

[0013] The argon atmosphere refers to the heating furnace being filled with argon to 0.03-0.05MPa.

[0014] The annealing treatment refers to the copper being placed in a heating furnace at 800° C. for 1 hour and then naturally cooled to below 50° C.

[0015] The ketoacid polishing liquid is a mixture of sulfuric acid and hydrochloric acid.

[0016] The first density glaze refers to a mixed powder of silica (SiO2), alumina (Al2O3), zirconium oxide (ZrO2), sodium oxide (Na2O), potassium oxide (K2O), and titanium dioxide (TiO2) at a ratio of 60wt%, 25wt%, 3wt%, 2wt%, 5wt%, and 5wt% (based on the total mass of silica powder, alumina powder, zirconium oxide powder, sodium oxide powder, potassium oxide powder, and titanium dioxide powder), with a powder particle size less than 300 mesh. Add water to the mixed powder until the density is 2.5g / cm3 to obtain a first density glaze.

[0017] The second density glaze refers to a mixed powder of silica (SiO2), alumina (Al2O3), zirconium oxide (ZrO2), sodium oxide (Na2O), potassium oxide (K2O), and titanium dioxide (TiO2) at a ratio of 60wt%, 25wt%, 3wt%, 2wt%, 5wt%, and 5wt% (based on the total mass of silica powder, alumina powder, zirconium oxide powder, sodium oxide powder, potassium oxide powder, and titanium dioxide powder), and the powder particle size is less than 300 mesh. Add water to the mixed powder until the density reaches 4.5g / cm3.

[0018] The temperature rise procedure refers to starting from room temperature, raising the temperature by 20°C per minute, raising the temperature to 900°C and maintaining it for 5-10 minutes before naturally cooling down.

[0019] The invention has the advantages of providing a method for firing a glass insulating layer on the surface of oxygen-free copper, wherein silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium oxide (ZrO2), sodium oxide (Na2O), potassium oxide (K2O), and titanium dioxide (TiO2) are mixed according to a certain specific gravity, and then water is added to prepare a glaze of a certain density, and the oxygen-free copper after grinding, annealing, and pickling is glazed by dipping, and then fired in an argon atmosphere. The obtained glass insulating layer has the characteristics of high bonding strength with the copper surface, low sputtering of the glass insulating layer in a plasma discharge cavity, high withstand voltage, etc., and the method is applicable to both flat copper and curved copper, and has great application prospects. DETAILED DESCRIPTION

[0020] The present invention is described in detail below in conjunction with specific embodiments. However, the following embodiments are limited to explaining the present invention, and the protection scope of the present invention should include the entire contents of the claims, and through the description of the following embodiments, those skilled in the art can fully implement the entire contents of the claims of the present invention.

[0021] The embodiments of the present invention are described in detail below.

[0022] A method for firing a glass insulating layer on the surface of oxygen-free copper comprises the following steps:

[0023] (1) After the oxygen-free copper surface of any cross section is polished with 2000 mesh metallographic sandpaper with aluminum oxide as abrasive, the oxygen-free copper is placed in a heating furnace with an argon atmosphere of 0.03-0.05 MPa for annealing; the annealed oxygen-free copper surface is immersed in a copper acid polishing liquid mixed with sulfuric acid and hydrochloric acid for 40-60 seconds for pickling;

[0024] (2) immersing the pickled oxygen-free copper into a pre-prepared low-density glaze for glazing treatment; after the oxygen-free copper treated in the low-density glaze is naturally air-dried, immersing it in a pre-prepared high-density glaze for secondary glazing treatment;

[0025] (3) The oxygen-free copper surface after the secondary glaze treatment is naturally air-dried and then placed in a heating furnace for vacuum sealing;

[0026] (4) After the vacuum degree in the heating furnace is evacuated to below 1Pa, the heating program is started; when the temperature in the heating furnace rises to 290-300°C, the vacuum angle valve is closed to stop evacuation, and then argon gas is filled into the heating furnace to 0.05MPa; the heating furnace continues to heat up to 900°C and maintains for 10 minutes before naturally cooling down; after the natural temperature drops to below 50°C, the oxygen-free copper is taken out, and the work of firing the insulating glass layer on the surface of the oxygen-free copper is completed.

[0027] The annealing treatment refers to the copper being placed in a heating furnace at 800° C. for 1 hour and then naturally cooled to below 50° C.

[0028] The ketoacid polishing liquid is a mixture of sulfuric acid and hydrochloric acid;

[0029] The low-density glaze refers to a mixed powder of silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium oxide (ZrO2), sodium oxide (Na2O), potassium oxide (K2O), and titanium dioxide (TiO2) according to 60wt%, 25wt%, 3wt%, 2wt%, 5wt%, and 5wt% (based on the total mass of silicon dioxide powder, aluminum oxide powder, zirconium oxide powder, sodium oxide powder, potassium oxide powder, and titanium dioxide powder), with a powder particle size of less than 300 meshes. A proper amount of water is added to the mixed powder until the density is 2.5g / cm 3 Low-density glaze;

[0030] The high-density glaze refers to a mixed powder of silicon dioxide (SiO2), aluminum oxide (Al2O3), zirconium oxide (ZrO2), sodium oxide (Na2O), potassium oxide (K2O), and titanium dioxide (TiO2) at 60wt%, 25wt%, 3wt%, 2wt%, 5wt%, and 5wt% (based on the total mass of silicon dioxide powder, aluminum oxide powder, zirconium oxide powder, sodium oxide powder, potassium oxide powder, and titanium dioxide powder), with a powder particle size of less than 300 meshes. A proper amount of water is added to the mixed powder until the density reaches 4.5g / cm 3 .

[0031] The temperature rise procedure is to start from room temperature, increase the temperature by 20°C per minute, increase the temperature to 890-900°C and maintain it for 5-10 minutes before naturally cooling down.

[0032] Example 1: Process for firing a glass insulation layer on the surface of a Φ6mm copper wire

[0033] The process steps for firing the glass insulation layer on the surface of Φ6mm copper wire are as follows:

[0034] 1) The surface of the copper wire was polished with metallographic sandpaper with 2000 molybdenum and aluminum oxide as abrasive, and the polished copper wire was placed in a heating furnace with an argon atmosphere of 0.03 MPa for annealing, the argon purity was 99.9%, the annealing temperature was 800° C., the time was 1 hour, and then the temperature was lowered to below 50° C.; the cooled copper wire was immersed in a mixture of hydrochloric acid and sulfuric acid for pickling, and the pickling time was 60 seconds;

[0035] 2) The pickled copper wire is immersed in a pre-prepared low-density glaze for the first glazing treatment. The low-density glaze is a mixture of silicon dioxide, aluminum oxide, zirconium oxide, sodium oxide, potassium oxide, and titanium dioxide powders with a particle size of less than 300 molybdenum in the proportion of 60wt%, 25wt%, 3wt%, 2wt%, 5wt%, and 5wt% water to a density of 2.5g / cm 3 After the first glazing, the copper wire is naturally air-dried, and then immersed in a pre-prepared high-density glaze for a second glazing treatment. The high-density glaze is a powder of silicon dioxide, aluminum oxide, zirconium oxide, sodium oxide, potassium oxide, and titanium dioxide with a particle size of less than 300 molybdenum, according to 60wt%, 25wt%, 3wt%, 2wt%, 5wt%, and 5wt% water to prepare a density of 4.5g / cm 3 Mixed liquid;

[0036] 3) The copper wire after the glaze treatment is naturally air-dried, and then placed in a heating furnace for vacuum sealing;

[0037] 4) The vacuum degree in the heating furnace is evacuated to below 1Pa, and then the heating furnace starts to heat up at 20°C per minute. When the temperature in the heating furnace rises to 300°C, the vacuum angle valve is closed to stop the vacuuming, and then argon gas with a purity of 99.9% is filled into the heating furnace to 0.05MPa. During the above process, the heating furnace is heated at a heating rate of 20°C per minute. After the heating furnace continues to heat up to 900°C and maintains for 10 minutes, it is cooled naturally; after the temperature naturally cools to 50°C, the copper wire is taken out, and the work of firing the insulating glass layer on the copper surface is completed. The thickness of the glass insulating layer can reach more than 50μm, and the Vickers hardness test is HV 0.5 507.

[0038] The present invention does not elaborate on some of the common technologies of those skilled in the art. The above-described embodiments are only descriptions of preferred implementations of the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementations described. Without departing from the design spirit of the present invention, various modifications and improvements made by ordinary technicians in this field to the technical solution of the present invention should fall within the scope of protection determined by the claims of the present invention.

Claims

1. A method for sintering a glass insulating layer on the surface of oxygen-free copper, characterized in that: The method can produce a glass insulating layer on the copper surface that is resistant to high temperature, high pressure, low secondary electron emission coefficient, plasma sputtering, and has high bonding strength with the copper surface, and can meet the special application requirements in the field of built-in inductively coupled radio frequency ion source accelerator and ion cleaning; the method comprises the following steps: (1) grinding the surface of oxygen-free copper; placing the ground oxygen-free copper in a heating furnace in an argon atmosphere for annealing; immersing the annealed oxygen-free copper surface in a copper acid polishing solution for 40-60 seconds for pickling; the annealing process refers to the oxygen-free copper being heated in a furnace at 800°C for 1 hour and then naturally cooled to 50°C; (2) The oxygen-free copper after pickling is immersed in a first density glaze for dipping treatment; the copper treated in the first density glaze is naturally air-dried and then immersed in a second density glaze for secondary dipping treatment; wherein the first density is less than the second density; the first density glaze refers to a mixed powder of 60wt%, 25wt%, 3wt%, 2wt%, 5wt% and 5wt% of silicon dioxide, aluminum oxide, zirconium oxide, sodium oxide, potassium oxide and titanium dioxide, based on the total mass of silicon dioxide powder, aluminum oxide powder, zirconium oxide powder, sodium oxide, potassium oxide and titanium dioxide powder, and the powder particle size is less than 300 mesh; the mixed powder is added with water until the density is 2.5g / cm 3 The first density glaze of the second density glaze refers to the total mass of silicon dioxide powder, aluminum oxide powder, zirconium oxide powder, sodium oxide powder, potassium oxide powder and titanium dioxide powder, silicon dioxide, aluminum oxide, zirconium oxide, sodium oxide, potassium oxide, titanium dioxide according to 60wt%, 25wt%, 3wt%, 2wt%, 5wt%, 5wt% mixed powder, the powder particle size is less than 300 mesh, the mixed powder is added with water until the density reaches 4.5g / cm 3 ; (3) Allow the oxygen-free copper surface after the secondary glaze treatment to air dry naturally, and then place it in a heating furnace for vacuum sealing; (4) After the vacuum degree in the heating furnace is evacuated to below 1Pa, the heating program is started; when the temperature in the heating furnace rises to 290-300°C, the vacuum angle valve is closed to stop evacuation, and then argon is filled into the heating furnace to 0.05-0.07MPa; the heating furnace continues to heat up to 890-900°C and maintains for 5-10 minutes before naturally cooling down; after the temperature naturally drops to below 50°C, the oxygen-free copper is taken out to complete the firing of the insulating glass layer on the surface of the oxygen-free copper.

2. The method for sintering a glass insulating layer on the surface of oxygen-free copper according to claim 1, characterized in that: In step (1), the surface of the oxygen-free copper is polished with metallographic sandpaper, wherein the particle size of the metallographic sandpaper is 2000 mesh and the abrasive is aluminum oxide.

3. The method for sintering a glass insulating layer on the surface of oxygen-free copper according to claim 1, characterized in that: In step (1), the argon atmosphere refers to the heating furnace being filled with argon to a concentration of 0.03-0.05 MPa, and the purity of the argon is 99.9%.

4. The method for sintering a glass insulating layer on the surface of oxygen-free copper according to claim 1, characterized in that: In step (1), the copper acid polishing solution refers to a mixture of sulfuric acid and hydrochloric acid.

5. The method for sintering a glass insulating layer on the surface of oxygen-free copper according to claim 1, characterized in that: In step (4), the temperature rise procedure refers to starting from room temperature, raising the temperature by 20°C per minute, raising the temperature to 890-900°C and maintaining it for 5-10 minutes before naturally cooling down.